Design and evaluation of additively manufactured parts with three dimensional continuous fibre reinforcement. (15th January 2016) - Brooks, Hadley; Molony, Samuel
Abstract: Additive manufacturing (AM) provides many benefits such as reduced manufacturing lead times, streamlined supply chains, part consolidation, structural optimisation and improved buy-to-fly ratios. Barriers to adoption include high material and processing costs, low build rates, isotropic material properties, and variable processing conditions. Currently AM polymer parts are far less expensive to manufacture than AM metal parts, therefore improving the properties of polymer parts is highly desirable. This paper introduces a design methodology used to integrate continuous reinforcement into AM polymer parts with the aim of improving their mechanical properties. The method is validated with the design and testing of three case studies, a pulley housing, hook and universal joint used to demonstrate the applicability of the method for tensile, bending and torsion loading types respectively. Physical testing showed that it was possible to improve the strength of parts by over 4000%, elongation to failure by over 2000% and stiffness by approximately 200%. In addition a method of integrating condition monitoring capabilities into the parts was demonstrated. An analysis of the specific strength of the parts suggests that the reinforced parts are comparable to aluminium alloys, suggesting that in some cases AM polymer composite parts could supplant more costly metal parts. Graphical abstract: Evolution of a pulley design from left to right: a) volumetric design space, b) topological optimisation, c) FEA of fibre reinforced part, d) final iteration after first physical tests. Highlights: New design methodology for AM parts with continuous reinforcement Verified methodology with three case studies Improved strength by over 4000% and elongation to failure by over 2000% Introduced method of integrating sensors